Green Chemistry 2018
DOI: 10.5772/intechopen.70421
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Green Corrosion Inhibitors for Industrial Metals and Alloys

Abstract: Present chapter describes recent advances in the field of development of ionic liquids as green and sustainable corrosion inhibitors for metals and alloys. The present chapter has been divided into several sections and subsections. Recently, development of the green and sustainable technologies for the corrosion prevention is highly desirable due to increasing ecological awareness and strict environmental regulations. In the last two decades, corrosion inhibition using ionic liquids has attracted considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 149 publications
(167 reference statements)
0
26
0
Order By: Relevance
“…The corrosion inhibition efficiency of Bombax ceiba flower extracts was calculated using the following eqn. [26]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion inhibition efficiency of Bombax ceiba flower extracts was calculated using the following eqn. [26]:…”
Section: Resultsmentioning
confidence: 99%
“…Various organic inhibitors have been synthesized and used to inhibit metal corrosion in acidic solutions. Some of these organic inhibitors are expensive, toxic, hazardous and harmful for human beings and environment as well [5][6][7]. The toxicity of organic inhibitors may manifest either during the synthesis of the organic molecules or when it used.…”
Section: Introductionmentioning
confidence: 99%
“…Both the ligand and its metal complexes were tested against some microorganisms for their antimicrobial activity. been investigated using weight loss and electrochemical methods by Verma et al, [79].These compounds showed maximum efficiency of 92% and 95% at 25ppm concentration respectively. Potentiodynamic polarization suggested that the inhibitors depict mixed type behaviour.…”
Section: Metal Complexes Of Mannich Basesmentioning
confidence: 99%
“…The ILs have several effective properties, including low volatility, very high stability, capability to dissolve a wide range of inorganic and organic compounds, capability to solubilize gases like CO 2 , H 2 , CO etc., dependency of solubility on the nature of anions and cations . ILs have also been used in different fields such as batteries and capacitors, fuel cells, photovoltaics, extractions and separations , optical sensors and electrochemical sensors . The utilization of ILs as modifiers to surfaces of electrochemical sensor increases the sensitivity, stability and selectivity of the reduction and/or oxidation of chemical compounds .…”
Section: Introductionmentioning
confidence: 99%